The Process of Self-Acceptance in Patients with Paranoid Schizophrenia - Putri, Siavina Meiliana; Wahyuni, Endang; Pribadi, Eko Teguh (International Conference on Sustainable Health Promotion, 2025)
Self-acceptance is an important aspect for paranoid schizophrenic patients because it affects their ability to adaptand their quality of life. This study aims to describe the process of self-acceptance in paranoid schizophrenic patients. A qualitative design was used with semi-structured interviews of patients diagnosed with paranoid schizophrenia who were undergoing treatment at a mental hospital in East Java. The results showed that the subjects experienced five stages of self-acceptance, including aversion, curiosity, tolerance, allowing, and friendship. The subjects also experienced emotional dynamics: denial, anger, bargaining, depression, and acceptance. The implications of this study on the self-acceptance process of paranoid schizophrenia patients, through interrelated cognitive and emotional stages, are not always linear and require time and environmental support. The results of this study are expected to contribute to the development of psychological interventions to support the self-acceptance process in patients with similar disorders.